A Comparative Study of Waffle Slab - MD Parvej Aalam, Neeraj Kumar Sahu (Mathematical Statistician and Engineering Applications, 2023)
Waffle panels are often designed to assemble floors and ceilings while covering longer spaces within a building without dilemma or support. Structural engineers analyse slabs like trusses as realistically supported systems (all four corners) and derive answers based on beam or slab displacement compatibility to get approximate answers or slab girders. Refine with . Perform a comprehensive finite element analysis (FEM). A device with he one of the most generalized finite detail software available on the market. This is because there is no analytical solution or simple calculation tools except for slabs where all edges are seriously supported. Based on this observation, a comparative analysis of ribs and waffle plates is presented to determine maximum stability and distribution within the evaluation. To validate the results, selected instances are compared using finite detail analysis, and force, second, displacement, and flow results are compared for each trace.